Diseño de un manual de organización y funciones para mejorar la gestión administrativa en la fábrica Minerales Industriales Loyola de la provincia de Loja - Panamito Coronel, Ener Ronaldo (2023)
The purpose of this research is to contribute to the improvement of administrative management, with the main objective of designing an Organization and Functions Manual to improve administrative management in the "Minerales Industriales Loyola" factory, in Catamahillo, Zapotillo canton, Loja province. . For its fulfillment, the qualitative, quantitative and descriptive approaches were used; likewise, techniques such as observation, interview and survey, the same ones that allowed a diagnosis of the current situation of the factory and its organization in each of the positions. The instruments used is the interview with the Manager and through a survey addressed to the 25 workers, of which 22 belong to the operational area and three to the administrative area of the factory, where it was evidenced that the non-existence of the organization and functions manual It is having an impact on the work performance of workers, directly affecting the service provided by the factory. For this reason, a proposal for a Manual for the Organization of Functions was proposed, which contains information such as the identification of the position, hierarchical relationship, main functions and responsibilities for each of the positions that the factory has, the same ones that conform to the needs of the “Loyola Industrial Minerals” factory. Keywords: MOF Organizations and Functions Manual, organizational structure, function sheet.